Design and evaluation of magnetic-targeted bilosomal gel for rheumatoid arthritis: flurbiprofen delivery using superparamagnetic iron oxide nanoparticles - Mushtaq, Rayan Y.; Naveen, Nimbagal Raghavendra; Rolla, Krishna Jayanth; Al Shmrany, Humood; Alshehri, Sameer; Salawi, Ahmad; Kurakula, Mallesh; Alghamdi, Majed A.; Rizg, Waleed Y.; Bakhaidar, Rana B.; Abualsunun, Walaa A.; Hosny, Khaled M.; et al. (Frontiers in Pharmacology, 2024)
Introduction The study aimed to systematically enhance the fabrication process of flurbiprofen-loaded bilosomes (FSB) using Quality by Design (QbD) principles and Design of Experiments (DOE). The objective was to develop an optimized formulation with improved entrapment efficiency and targeted drug delivery capabilities. Methods The optimization process involved applying QbD principles and DOE to achieve the desired formulation characteristics. Superparamagnetic iron oxide nanoparticles (SPIONs) were incorporated to impart magnetic responsiveness. The size, entrapment efficiency, morphology, and in vitro release patterns of the FSB formulation were evaluated. Additionally, an in situ forming hydrogel incorporating FSB was developed, with its gelation time and drug release kinetics assessed. In vivo studies were conducted on osteoarthritic rats to evaluate the efficacy of the FSB-loaded hydrogel. Results The optimized FSB formulation yielded particles with a size of 453.60 nm and an entrapment efficiency of 91.57%. The incorporation of SPIONs enhanced magnetic responsiveness. Morphological evaluations and in vitro release studies confirmed the structural integrity and sustained release characteristics of the FSB formulation. The in situ forming hydrogel exhibited a rapid gelation time of approximately 40 ± 1.8 s and controlled drug release kinetics. In vivo studies demonstrated a 27.83% reduction in joint inflammation and an 85% improvement in locomotor activity in osteoarthritic rats treated with FSB-loaded hydrogel. Discussion This comprehensive investigation highlights the potential of FSB as a promising targeted drug delivery system for the effective management of osteoarthritis. The use of QbD and DOE in the formulation process, along with the integration of SPIONs, resulted in an optimized FSB formulation with enhanced entrapment efficiency and targeted delivery capabilities. The in situ forming hydrogel further supported the formulation’s applicability for injectable applications, providing rapid gelation and sustained drug release. The in vivo results corroborate the formulation’s efficacy, underscoring its potential for improving the treatment of osteoarthritis.